MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN IPA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN VISUAL, AUDITORI, KINESTHETI(VAK) PADA MATERI SISTEM GERAK MANUSIA DI KELAS VI SD NEGERI 067241 MEDAN DENAI: Penelitian Tindakan Kelas - Anida Fauziah; M Fauzi Hasibuan; Yendrawaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study investigates the low learning outcomes of students in the subject of Science and Social Studies (IPAS), particularly on the topic of the human motion system, in grade VI at UPT SD Negeri 067241 Medan Denai. The research aims to improve learning outcomes through the implementation of the Visual, Auditory, Kinesthetic (VAK) learning model. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which involves four stages: planning, action, observation, and reflection. The subjects of this study are 28 sixth-grade students. Data were collected through observation and tests. The results showed a significant improvement after the implementation of the VAK model. Before the intervention, only 28.57% of students met the Learning Achievement Criteria (KKCP). This percentage increased to 62% in cycle I and reached 89.29% in cycle II. The average student score also increased from 63 in the pre-intervention stage to 67.14 in cycle I and 85 in cycle II, indicating the effectiveness of VAK in enhancing student learning outcomes.